Macrobenthos Community in the Littoral Zone Water Area of Iboih Beach Sabang, Aceh - Oktavia, Rita; Amin, Nurdian (Budapest International Research and Critics University, 2019)
The aim of this study is to know the macrobenthos community in the littoral zone water area of Iboih beach, Aceh. Sample collection is conducted by using plot size of 1 x 1 meter, destructive sampling and non-destructive sampling methods. The results shows that macrobenthos inventory on Rubiah Island in Sabang, Aceh with destructive sampling methods is amounted to 8 species from 5 families, while Benthos obtained from non-destructive sampling methods is amounted to 8 species from 6 families. Macrobenthos inventory on the water of natural tourism area of Iboih beach Sabang. Diversity index is moderate with H '= 1.22061, and non-destructive value H' = 1.31391. Includes the category of moderate diversity. In Payau waters with destructive H'= 1.74816, nondestructive with a value of H' = 1.7104. Has a moderate diversity index. Macroentent inventory of the Teupin Layeu Mangrove Waters of Sabang City found 27 and 29 species of benthos. Among them (Meretrik meretrik) is amounted to 44, (Anadara cunearca) is amounted to 36 and many other species. With species diversity H'= 3, 2114 indicates a high level of species diversity.